The relationship between workplace spirituality and individual spirituality with organizational commitment among Malaysian university administrators - Abd Majid, Izan Khairana; Abdul Rahman, Shukran (Sekolah Pascasarjana Universitas Muhammadiyah Jakarta, 2015)
Higher Learning Institutions (HLIs) have been undergoing many changes and development, giving impacts to the work process of university staff, and their work-related attitudes and well being. Studies have been conducted to look at relationship between organizational commitment among university administrators and its psychosocial predictors, such as spirituality at the workplace. Given the absence of such studies among non-western sample a research has been conducted to study the relationship between workplace spirituality and individual spirituality with organizational commitment. The findings of this study is useful to Human Resource managers to understand the significant role of workplace and individual spirituality in the development of organizational commitment and to design appropriate programs or interventions that will optimize the commitment of the employees.